Identification of Valerate as Carrying Capacity Modulator by Analyzing Lactiplantibacillus plantarum Colonization of Colonic Microbiota in vitro - Isenring, Julia; Stevens, Marc J. A.; Jans, Christoph; Lacroix, Christophe; Geirnaert, Annelies (Frontiers in Microbiology, 2022)
Humans ingest many microorganisms, which may colonize and interact with the resident gut microbiota. However, extensive knowledge about host-independent microbe-microbe interactions is lacking. Here, we investigated such colonization process using a derivative of the model probiotic Lactiplantibacillus plantarum WCFS1, into continuously cultivated gut microbiota in the intestinal PolyFermS fermentation model inoculated with five independently immobilized human adult fecal microbiota. L. plantarum successfully colonized and organized itself spatially in the planktonic, i.e. the reactor effluent, and sessile, i.e. reactor biofilm, fraction of distinct human adult microbiota. The microbiota carrying capacity for L. plantarum was independent of L. plantarum introduction dose and second supplementation. Adult microbiota (n=3) dominated by Prevotella and Ruminoccocus exhibited a higher carrying capacity than microbiota (n=2) dominated by Bacteroides with 105 and 103 CFU/ml of L. plantarum, respectively. Cultivation of human adult microbiota over three months resulted in decreased carrying capacity and correlated positively with richness and evenness, suggesting enhanced resistance towards colonizers. Our analyses ultimately allowed to identify the fermentation metabolite valerate as a modulator to increase the carrying capacity in a microbiota-independent manner. In conclusion, by uncoupling microbe-microbe interactions from host factors, we showed that L. plantarum colonizes the in vitro colonic community in a microbiota-dependent manner. We were further able to demonstrate that L. plantarum colonization levels were not susceptible to the introduction parameters dose and repeated administration but to microbiota features. Such knowledge is relevant to gain a deeper ecological understanding of colonizer-microbiota interactions and developing robust probiotic strategies.